(untitled) (Bangladesh Journal of Agricultural Research, 2018)
The eggplants (Solanum melongena L.) were cultivated in the field to investigate the abundance and diversity of insects. In total 488 insects were collected from the eggplant field during May to August 2016, which belonged to 20 species in 21 families and 10 orders. Among the taxonomic orders, Hemiptera was the most dominant followed by Coleoptera, Hymenoptera, and Diptera. The order Thysanoptera revealed the lowest abundance. The abundance, richness and diversity of pest, predator, pollinator and other categories of insects differed significantly and the pest revealed the highest abundance and richness compared to others. In total 9 species of insects belonged to 7 families of 4 orders were found as pest and their abundance varied from 0.1±0.1 to 4.6±0.9 /30 sweeps. In total 8 species of insects belonged to 8 families of 7 orders were found as predator and their abundance varied from 0.3±0.1 to 2.0±0.3/30 sweeps. Among the predator insects, lady bird beetle showed the highest abundance. In eggplant field, insects were highest and lowest abundant at 11.00 and 13.00 h of the day, respectively. Bangladesh J. Agril. Res. 43(4): 647-653, December 2018